Reflective analysis on patient safety in the hospital context and primary care - Ingrid Moura de Abreu, Priscila Martins Mendes, Ana Paula Mousinho Tavares, Fernanda Valéria Silva Dantas Avelino, Lidya Tolstenko Nogueira, Silvana Santiago da Rocha (Revista de Enfermagem da UFPI)
DOI: https://doi.org/10.26694/2238-7234.91106-110